Depressive symptoms and quality of life in breast cancer women - Valle, Rubén (2006)
Background: Breast cancer women have a tendency to develop psychiatric symptomatology, mainly depressive. A way to evaluate how the patient entails her disease is by quality of life. Objectives: To determine the prevalence of depressive symptoms and quality of life and their associations with time since diagnosis and the menopausal status. Design: Analytical, observational and transversal study. Setting: Arzobispo Loayza Hospital Oncology Service. Participants: Women with clinical and histological diagnosis of breast cancer and seeking chemotherapy. Interventions: The Beck depression inventory, the Mezzich and Cohen quality of life scale and a demographic questionnaire were used. The Fisher test, student’s T-test and lineal regression analysis were used. Main outcome measures: Depression symptoms, quality of life. Results: In 24 women studied the prevalence of depressive symptoms and low level of quality of life was 38%. We did not find a significant association between depressive symptoms and quality of life, except with education level, OR 11,2 (p= 0,047, 95%CI 0,99 to 125,6). Conclusions: We found a prevalence of 38% of both depressive symptoms and low level of quality of life. Time from diagnosis and menopausal status did not have a significant association with both depressive symptoms and quality of life. The only factor significantly associated to quality of life was patient’s education level.